Influence of the Cement Film Thickness on the Push-Out Bond Strength of Glass Fiber Posts Cemented in Human Root Canals - Natália Araújo Silva Prado; Reinaldo de Souza Ferreira; Marcos Henrique de Pinho Maurício; Sidnei Paciornik; Mauro Sayão de Miranda (International Journal of Dentistry)
The present study evaluated the influence of the cement film thickness on the push-out bond strength of glass fiber posts in the cervical, medium, and apical thirds of root canal spaces. Thirty roots were randomly divided into three groups, according to the fiber post system’s drills: (G1) #2; (G2) #3; (G3) #4. The posts were cemented using a self-adhesive cement, and a small amount of powdered Rhodamine B was used as a stain. Images of both sides of each slice were obtained before and after the push-out test. To determine the cement thickness, a macro routine was developed using the software KS 400. The data were analyzed statistically using Kruskal-Wallis and Dunn’s test. G2 (14.62±5.15 MPa) showed statistically higher bond strength values than G1 (10.04±5.13 MPa) and G3 (7.68±6.14 MPa). All groups presented higher bond strength values in the apical third. The bur diameter significantly influenced the results of the shear bond strength for the push-out test. The slight increase in the cement thickness allowed an increase in the values of shear bond strength when compared to very thin or very thick cement films.